Genomic and metagenomic analysis of the ongoing speciation between Priestia megaterium and Priestia aryabhattai - Spence, Sam (Nanyang Technological University, 2023)
Priestia megaterium and Priestia aryabhattai are two closely related groups of bacteria with important industrial uses, but it has been debated whether they are the same or different species. In this thesis, I aimed to resolve the identity of these two groups and reveal the functional and ecological differences between them. My phylogenetic study of 190 Priestia genome assemblies showed that the two groups are in separate evolutionary clades. The whole-genome genetic distance between them was sufficient to classify them as separate species; the presence of recombinant strains, isolated from environmental samples, suggests a still ongoing speciation. To examine the functional difference between the two species, I identified the orthologous genes in 14 P. aryabhattai and 13 P. megaterium complete genomes and compared the gene content of the two species. The results showed substantial amino acid sequence divergence between the two species in genes related to cobalamin synthesis, sugar transport, sporulation, and flagellar assembly. Genomes of P. aryabhattai also had increased copy numbers of several iron transport genes which are important for plant growth promotion. Species-specific genes were used to design PCR primers for the easily replicated identification of P. megaterium and P. aryabhattai isolates without whole-genome sequencing. Finally, a global metagenomics analysis showed that P. megaterium was the generally more abundant species, but that P. aryabhattai may have an ecological niche in Southeast Asia.